Water permeability of geopolymers emulsified with oil. (September 2020) - Planel, B.; Davy, C.A.; Adler, P.M.; Hauss, G.; Bertin, M.; Cantarel, V.; Lambertin, D.
Abstract: Recently, geopolymer (GP) cements have proven adequate to immobilize oil emulsions as GEOIL composites. When used for radioactive waste storage, the vicinity of GEOIL with Portland Cement (PC) concretes may induce leaching by the PC pore water. This research identifies the preferential water flow pathways, and quantifies the water permeability of hardened GEOIL mortars using a typical PC pore water. Two alkali-activated GP cements are used, either made of 100% metakaolin (MK) or of 80%MK-20% slag, for oil proportions of 0, 20, 40 or 60%vol. For the identification of the preferential water flow pathways, two water flow scenarii are investigated numerically. Either water flows through the oil emulsion (Scenario 1) or water flows through the GP cement mortar pores (Scenario 2). The 3D structure of the oil emulsion is quantified by X Ray micro-computed tomography (X Ray micro-CT), and the pore structure of GP cement mortars is identified by image analysis. Fluid pathways are predicted for both scenarii by 3D numerical simulations. Secondly, water permeability experiments are conducted on GEOIL mortars. Water permeability K water of highly alkaline PC water is deduced over several weeks. The results validate Scenario 2; for 20 or 40%vol oil, water flows preferentially through the GP cement mortar pores (at a permeability below 10 −18 m 2 ), instead of through the percolating oil emulsion. Finally, experiments show that K water for the GP cement mortar made of 80%MK-20%GGBFS does not remain stable over time when added with 20%vol oil. Comparatively, for the 100%MK GP cement mortar with 20%vol oil, a stable K water is recorded for 40 days. Whatever the oil percentage, the initial K water value is identical and smaller than without oil. A dedicated experiment shows that the oil additives (surfactants) are very probably responsible for this behaviour. At 60%vol oil, water and organic matter flow progressively out of the GEOIL composite.